A clinical study of neonatal birth injuries in a tertiary care hospital-NICU, Bijapur - -, Rizwan-u-zama; Jeergal, Nazeer Ahmad; Thobbi, A N; Katti, Sumedha Vijay (Indian Journal of Child Health, 2020)
Background: Neonatal birth injuries are the third major cause of neonatal mortality in most developing countries. Very few studies have been done in India on birth injuries and its relation to various factors such as undesirable presentations and parity. Aim: The present study was conducted to analyze the birth injuries in our setup to know the various perinatal circumstances leading to birth injuries. Materials and Methods: An observational study was done in which 100 cases of birth trauma were noticed among 850 consecutive viable births during the study period of 2 years. Details of the health status of the mother, antenatal, intra-natal, and postnatal particulars, including the age, sex, weight, mode of delivery, type of presentation, and nature of the birth injury in different modes of delivery and type of presentation of the baby were taken. Results: It was found that of 850 newborn babies, 100 babies were found to have birth injuries, thus giving an incidence of 11.76% per 100 live births. Asphyxia formed the major groups which were noted in 45 babies. Cephalohematoma was the next common injury being noted in 32 cases. A total of 18 babies had soft tissue injuries and 4 babies had neurological injuries. Conclusion: Our findings support to use data on neonatal birth injuries as an indicator to assess the quality and safety of maternity units.